Prevalence of Syphilis Cases Among Blood Donors in Bojonegoro (Jurnal Ilmu Kesehatan Masyarakat, 2022)
Syphilis is a disease caused by Treponema pallidum. Syphilis could transmit through sexual intercourse, and can also occur in the vertical direction from the mother to the fetus, through blood products and, in some cases, through medical equipment. Among those, blood transfusions are the main way to spread the disease. WHO estimates that more than 1 million people worldwide are diagnosed with 4,444 sexually transmitted diseases daily. This study was using total 51351 blood sample obtained from blood donor in 2020 and 2021 in Blood Donor Unit (UDD PMI) Bojonegoro. The aim in this study was to find the prevalence of syphilis cases occurred in Blood Donor Unit (UDD PMI) Bojonegoro. This finding may have implication to increase people awareness in syphilis. This study was used descriptive study with cross sectional design and conducted by using cross tabulation as statistical analysis. The data showed that there was slight increase with 0.12% and 0.16% cases of confirmed syphilis in 2020 and 2021 respectively (P = 0,174). Total cases from 51351 blood samples, 71 (0,14%) blood samples were positive for syphilis. The highest cases in 2020 was occurred in January (7 cases) and highest cases in 2021 was occurred in October (13 cases). The conclusion of this study showed that the prevalence of syphilis was low in this study. Even though the percentage might be below 1% in this study, it is still a significant transfusion problem in blood donation quality purpose to be overcomed.